PERAN GURU DALAM PENGEMBANGAN MEDIA PEMBELAJARAN PADA MATA PELAJARAN SOSIOLOGI DI SMAN 4 SUNGAI RAYA - Dewi Setyawati; Warneri Warneri; Sri Buwono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aims to determine, "The Role of Teachers in the Development of Learning Media in Sociology Subjects in SMA Negeri 4 Sungai Raya, Kuburaya Regency". The research method used is descriptive with a form of qualitative research. Data sources of this research are primary data sources and secondary data sources. Data collection techniques used were observation, interview and documentation techniques. While the data collection tools used are observation guidelines, interview guidelines and documentation. The analysis in this study was presented in a qualitative descriptive manner with the use of 4 informants, with the results of the study as follows: before having electricity facilities Teachers in teaching using visual learning media, after having electricity facilities Teachers in teaching using projector learning media. The teacher has developed the function of instructional media by clarifying the presentation of messages and information, increasing and directing attention so as to cause motivation to learn, and provide a common experience to students. Keywords: Teacher Role, Learning Media Development, High.